Appendisitis Akut pada Perempuan Usia 18 Tahun: Laporan Kasus - St Ramadina Puteri Tri Tiro Pasigai; Berry Erida Hasbi; Erwin Syarifuddin (KOLONI, 2026)
Appendicitis is an inflammation of the vermiform appendix that is generally caused by a bacterial infection process. This disease is one of the most common causes of acute abdominal surgical emergencies. Delayed diagnosis may increase the risk of perforation and postoperative complications. This case report aims to describe the clinical presentation, diagnosis, and management of acute appendicitis in a patient. This study used a descriptive design in the form of a case report involving an 18-year-old female patient who presented with right lower quadrant abdominal pain accompanied by nausea and vomiting. Clinical examination revealed typical signs of acute appendicitis with an Alvarado score of 7. Laboratory examination showed leukocytosis, while abdominal ultrasonography and abdominal MSCT findings supported the diagnosis of acute appendicitis. Following appendectomy, the patient’s clinical condition showed significant improvement. Right lower quadrant abdominal pain gradually decreased, and the patient’s vital signs remained stable. Gastrointestinal function also gradually recovered, as indicated by good dietary tolerance and the return of bowel movements. The patient demonstrated a good prognosis without postoperative complications such as perforation, intra-abdominal abscess, or surgical site infection. The patient was discharged in stable condition with oral antibiotics, analgesics, and outpatient follow-up education. This case demonstrates that early diagnosis of acute appendicitis is essential to prevent serious complications such as perforation and peritonitis.